Analisis Problematika Pembelajaran dan Perilaku Belajar Siswa Dalam Pelaksanaan Pembelajaran Pendidikan Pancasila Kelas V Sekolah Dasar - Sri Nurhayati; Dina Syafifah; Wandri Ramadhan (Journal of Curriculum and Pedagogic Studies (JCPS), 2026)
The purpose of this research is to describe and analyze various learning problems and student behavior in the implementation of Pancasila Education at fifth grade of SDN 09 Saruaso. This study employed a descriptive qualitative approach. The research subjects consisted of fifteen students and the class teacher. Data were collected through observation, interviews, and documentation. The data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The study's findings indicate that the learning problems identified include low levels of student motivation and participation, the application of teacher-dominated instructional approaches, limited media and learning resources, and a lack of student understanding in implementing Pancasila values in everyday life. In addition, various student behavioral problems were also found, such as lack of discipline, low attitudes of responsibility and mutual cooperation, lack of respect for friends, and a tendency to disrupt the learning process. These problems are influenced by both external and internal factors. Therefore, improvement efforts are needed through the adoption of more varied, active, and context-based learning methods, the use of relevant learning media, and strengthening cooperation between schools and families to support character building and enhance the quality of Pancasila instruction. Fifteen students and the class teacher served as research subjects in this descriptive qualitative study. Observation, interviews, and documentation were used to gather data. The Miles and Huberman model, which comprises data reduction, data presentation, and conclusion drawing, was used in the data analysis. The study's conclusions show that learning problems found encompass low levels of student motivation and student engagement during lessons, the application of teacher-dominated instructional approaches, limited media and learning resources, and a lack of student understanding in implementing Pancasila values ​​in everyday life. In addition, various student behavioral problems were also found, such as lack of discipline, low attitudes of responsibility and mutual cooperation, lack of respect for friends, and a tendency to disrupt the learning process. These problems are influenced by both external and internal elements, resulting in improvement efforts are needed through the adoption of more varied, active, and context-based learning methods, the use of relevant learning media, and strengthening cooperation between schools and families to support character building and enhancing the quality of Pancasila instruction.